Prospeksi Peradilan Tata Usaha Militer dalam Sistem Peradilan di Indonesia - Erni Agustina (Fakultas Hukum Universitas Islam Indonesia, 2009)
This research describes the lack of law of military administration wich is accord to article 353, act 31, 1997, enacted in Oct 15, 2000. this military administration afforementioned has not been put into effect more than 9 years, where by created law and social problems within military institution it self, such as decreasing individual soldier right as well as the existence of civil court body. The main problem in this research focus in the essential and prospect of the existence for military administration in the Indonesia justice system. The emergence problem particularly caused by 2 factors, ie:1. The absence of regulation for executing military administration.2. The damage of individual soldier right, as well as the essential existence of civil court body.Key word : Military, administration, justice system in Indonesia